2018
DOI: 10.1002/mnfr.201701038
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamyl Isobutyrate Decreases Plasma Glucose Levels and Total Energy Intake from a Standardized Breakfast: A Randomized, Crossover Intervention

Abstract: ScopeCinnamon is associated with anti‐obesity effects, regulating food intake, improving plasma glucose levels and lipid profiles in vivo. In the present study, the impact of cinnamyl isobutyrate (CIB), one constituent of cinnamon, on ad libitum food intake from a standardized breakfast and outcome measures of hormonal regulation of appetite were investigated.Methods and resultsIn this randomized, short‐term crossover intervention study, a 75 g per 300 mL glucose solution solely (control) or supplemented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…The cinnamon compounds tested included CAL, the major constituent of cinnamon bark oil, as well as its structural analogues or potential metabolites formed in vivo, CALC, CAC, and the cinnamic ester CIB. CIB was recently demonstrated to have an effect on total energy intake in a short-term human intervention study …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The cinnamon compounds tested included CAL, the major constituent of cinnamon bark oil, as well as its structural analogues or potential metabolites formed in vivo, CALC, CAC, and the cinnamic ester CIB. CIB was recently demonstrated to have an effect on total energy intake in a short-term human intervention study …”
Section: Discussionmentioning
confidence: 99%
“…CIB was recently demonstrated to have an effect on total energy intake in a short-term human intervention study. 22 To investigate the intestinal cellular uptake of the cinnamon constituents tested, an in vitro transport study using a differentiated confluent Caco-2 cell monolayer as the model for the intestinal barrier was carried out in a first step. In general, recovery in apical and basolateral compartments was low, probably because of the high volatility of the test compounds.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cinnamaldehyde is a compound found in cinnamon responsible for its particular flavor, which may improve metabolism owing to its reported hypoglycemic and lipid-lowering effects [136]. Two small randomized human clinical trials in healthy subjects showed that the acute ingestion of extracts of cinnamon (cinnamaldehyde [137] or cinnamyl isobutyrate, respectively [138]) increased energy expenditure (evaluated by indirect calorimetry) by~3.6 kcal over 90 min from ingestion [137] or reduced short-term energy intake by 4.6% [138], when compared to placebo. These changes are too small to be clinically relevant.…”
Section: Cinnamon Available Evidencementioning
confidence: 99%